2005
DOI: 10.1111/j.1740-0929.2005.00292.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of excess calcium as a different form on mineral metabolism in rats

Abstract: Excess calcium is known to affect the metabolism of other minerals. Calcium carbonate is the main source of calcium used in previous experiments that investigated excess calcium. Thus, it remains to be clarified whether other forms of calcium also have the same adverse effects. The effects of a high‐calcium carbonate diet or a high‐calcium citrate diet on mineral concentration in several tissues of rats were examined. Male rats aged 5 weeks were fed one of the experimental diets for 4 weeks. The control diet c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
12
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 29 publications
2
12
0
Order By: Relevance
“…); and Fe and Mg in rat bones (Takasugi et al . ). These reports indicated that changing dietary Ca level affected the availability of other minerals in fish and terrestrial animals, probably by competitive inhibition of these cations during intestinal absorption (Roy & Lall ).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…); and Fe and Mg in rat bones (Takasugi et al . ). These reports indicated that changing dietary Ca level affected the availability of other minerals in fish and terrestrial animals, probably by competitive inhibition of these cations during intestinal absorption (Roy & Lall ).…”
Section: Discussionmentioning
confidence: 97%
“…Simultaneous administration of dietary Ca induced a significant decrease in other bivalent minerals, such as Zn, Fe and Mn in vertebrae and Mg and Mn contents in scales. Increasing levels of dietary Ca also decreased Mg in the scales and vertebrae of Atlantic salmon (Vielma & Lall 1998); Fe, Zn and Mn in the vertebrae of scorpion fish (Hossain & Furuichi 2000a); Zn and Mg in the vertebrae and scales, respectively, of juvenile grouper (Ye et al 2006); and Fe and Mg in rat bones (Takasugi et al 2005). These reports indicated that changing dietary Ca level affected the availability of other minerals in fish and terrestrial animals, probably by competitive inhibition of these cations during intestinal absorption (Roy & Lall 2003).…”
Section: Aquaculture Nutritionmentioning
confidence: 99%
“…Our previous report showed that bone Zn concentration was increased and bone Mg concentration was decreased by excess Ca as carbonate but that these changes were not observed in the rats given the same amount of Ca as citrate [9]. Therefore, we hypothesized that the secondary Mg insufficiency increased bone Zn concentration in rats given excess Ca.…”
Section: Discussionmentioning
confidence: 85%
“…As mentioned above, bone Zn concentration was increased by the excess Ca as carbonate but not by the excess Ca as citrate [9]. Thus, carbonate itself possibly increases bone Zn concentration.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation